Multi-territory stroke preceded by pulmonary embolism with asymptomatic coronavirus disease 2019: a case report. Issue 12 (19th November 2021) - Van Herck, Jakob; Thoen, Hendrik; Delens, Christophe; Voet, Joeri
Abstract: Background: Non-bacterial thrombotic endocarditis is characterized by the presence of sterile vegetations on a cardiac valve. We present a case of multi-territory stroke caused by embolism of a non-bacterial thrombotic aortic valve endocarditis, leading to the diagnosis of a prostate adenocarcinoma with bone metastases. Case summary: A 66-year-old patient was diagnosed with pulmonary embolism, first attributed to an asymptomatic coronavirus disease 2019 infection. Edoxaban was started, which was discontinued by the patient. Four weeks later, he presented with subacute vertigo and balance disorders. Magnetic resonance imaging showed a multi-territory stroke. A transoesophageal echocardiogram demonstrated a small vegetation on the aortic valve with moderate aortic insufficiency. Blood cultures remained negative. Malignancy screening showed a markedly elevated prostate-specific antigen. Prostate adenocarcinoma was confirmed on biopsy. A positron emission tomography revealed metastatic disease. A diagnosis of non-bacterial thrombotic endocarditis and paraneoplastic pulmonary embolism secondary to prostate cancer was made. Edoxaban was restarted and the patient was referred for treatment of the prostate adenocarcinoma. Follow-up after 5 months showed no evidence of aortic valve vegetations. Discussion: Coronavirus disease 2019 in ambulatory patients may be insufficient as a predisposing factor for venous thrombo-embolism and these patients, especially the elderly, should undergo a screening for malignancy. Non-bacterial thrombotic endocarditis is a rare cause of multi-territory stroke. When related to cancer, the prostate can be the primary tumour.